Comment on “Examination of a Theoretical Model of Streaming Potential Coupling Coefficient” - P. W. J. Glover (International Journal of Geophysics)
Recently, Luong and Sprik published an article that compared measurements that had been made on 20 samples of saturated rock with a number of empirical models and Glover et al.’s 2012 theoretical model for zeta potential and streaming potential coefficient. They found that none of the empirical models could reproduce the streaming potential coefficient measurements which had been made in the presence of low pore fluid salinities, and the theoretical method could only do so if a constant zeta potential was invoked. This contribution in the form of a comment (i) indicates at least three possible errors in modelling that contribute to the mismatch between the theoretical model and the data at low salinities and (ii) carries out individual modelling on all of samples of Luong and Sprik’s 2014 dataset, showing that Glover et al.’s 2012 theoretical model matches the data well when the zeta potential is allowed to vary and good match can only be obtained with a constant zeta potential if an unrealistic value of zeta potential offset is used.